2022
DOI: 10.1177/23247096211065625
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Associated Ischemic Colitis: A Rare Manifestation of COVID-19 Infection—Case Report and Review

Abstract: Following the first report of COVID-19 infection in December 2019 as a respiratory illness, it has proven to be a multisystem disease. There are few reported cases of ischemic colitis with COVID-19 infection in the medical literature to date and we have limited understanding of its pathophysiology. We report 2 cases of ischemic colitis as the only manifestation of COVID-19. In addition, we review the current limited literature regarding COVID-19-associated ischemic colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Examination of the small bowel with mesenteric thrombosis revealed prominent endothelium, direct viral invasion of endothelial cells, and diffuse endothelial swelling with mononuclear cell infiltration [ 124 ]. Patients with severe COVID-19 infection and receiving inotropic agents can develop nonocclusive colonic ischemia due to severe vasoconstriction and reduced mesenteric blood flow [ 127 ].…”
Section: Reviewmentioning
confidence: 99%
“…Examination of the small bowel with mesenteric thrombosis revealed prominent endothelium, direct viral invasion of endothelial cells, and diffuse endothelial swelling with mononuclear cell infiltration [ 124 ]. Patients with severe COVID-19 infection and receiving inotropic agents can develop nonocclusive colonic ischemia due to severe vasoconstriction and reduced mesenteric blood flow [ 127 ].…”
Section: Reviewmentioning
confidence: 99%
“…It is now well known that SARS-CoV-2 infection can cause gastrointestinal symptoms in 12% up to more than 60% of patients [ 3 , 4 ], and, in some, they can even precede or be present without respiratory symptoms [ 5 ]. Most common gastrointestinal symptoms of COVID-19 are diarrhea, nausea, and vomiting [ 6 ], and symptoms of hemorrhagic colitis were reported only in several cases so far [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…suggesting the important role of microvascular obstruction in these patie [147,149,157,160,165,166]. In the recent review of Oja et al [160], the thrombosis of SMA was found in 24.9% of cases.…”
Section: Small Bowel Ischemia and Ischemic Colitismentioning
confidence: 95%
“…Almost half of the patients with small bowel ischemia in this study died. However, in most of the published cases of small bowel and colic ischemia, no evidence of arterial or venous acute thrombosis was found, suggesting the important role of microvascular obstruction in these patients [ 147 , 149 , 157 , 160 , 165 , 166 ]. In the recent review of Oja et al [ 160 ], the thrombosis of the SMA was found in 24.9% of cases.…”
Section: Vascular Abdominal Extrapulmonary Complicationsmentioning
confidence: 99%
See 1 more Smart Citation